Activeness Analysis Learns Elementary School Student On Online Learning During The Pandemic - Trisno Yuwono; Ana Andriani (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Lack of student education activeness in online learning during the pandemic is the background of this research. This study aims to provide an overview of how active elementary school students learn in online learning during the Covid-19 Pandemic and find out the factors causing the lack of student learning activeness in online education. The type of research used is literature study research. The data collection technique used is to collect theoretical studies and references sourced from articles and journals that have been accredite. This literature uses literature published in 2020-2021which can be accessed in full text in pdf format. The criteria for the articles reviewed are articles in Indonesian language research journals with the subject of student activity. Based on the results of literature research from several journals that have been written by previous researchers, it shows that in online learning, student activity is influenced by several factors, namely factors from teachers, parents, and students themselves.